TRANSPORTATION, PLANNING & PROMOTION IN FORT TOURISM OF MAHARASHTRA (International Journal of Food and Nutritional Sciences, 2022)
Maharashtra is one of the prosperous states in India. It also has historical and cultural heritage.Tourism is one of the momentous issues in developing countries. It is a great source of gaining of foreigncurrency and also it create various employment opportunities. Maharashtra has many of Forts monumentswhich help to acquire and preserve the history of that time. Also in this modern era of globalization forttourism in Maharashtra is widely growing global industry with bright prospectus and future.This research paper deals with the various aspects of Fort Tourism in Maharashtra. Also this paperthrows the lights on importance of Transportation in Fort Tourism of Maharashtra.